THE RELATIONSHIP BETWEEN LEARNING MOTIVATION, LEARNING INDEPENDENCE, AND LEARNING ENVIRONMENT WITH MATHEMATICS LEARNING OUTCOMES OF EIGHT GRADE STUDENT OF SMP MUHAMMADIYAH BANTUL - Fitria Rahmayanti; Edi Prajitno (Universitas Ahmad Dahlan, 2017)
independence and learning environment are some of the factors possibly related to mathematics learning outcomes. This research aims to know about is there any positive correlation and significance or not between learning motivation, learning independence, and learning environment with mathematics learning outcomes of eight grade students of SMP Muhammadiyah Bantul in odd semester in the academic year of 2016/2017. The population in this research was the students of VIII grade in SMP Muhammadiyah Bantul in the academic year of 2016/2017, consisted of class VIIIA, VIIIB, VIIIC, VIIID, and VIIIE totaling 145 students. Samples were taken from VIIID as the research sample class and with the random sampling technique. The writer uses a questionnaire method to collect the data of learning motivation, learning independence, and learning environment and test methods to get the result learning of math. The research instrument: validity test, different power test, and reliability test. Test requirement analysis includes a test of normality, a test of linearity, and the test of independence. The writer uses product-moment correlation analysis and multiple linear regression analysis to analyze the data. The results showed that there was a positive and significant relationship between learning motivation, learning independence, and learning environment with mathematics learning outcomes of eight grade students of SMP Muhammadiyah Bantul in odd semester in the academic year of 2016/2017. It is showed by Fcount= 12,6752 and Ftable = 2,98 so Fcount Ftable with R = 0,7707 and R2 = 0,5939 with = -117,6784 + 0,7637X1 + 0,5845X2 + 0,5046X3 , with SR X1 = 53,24%, SR X2 = 28,7006% and SR X3 = 18,0594%, SE X1 = 31,6199%, SE X2 = 17,0457% and SE X3 = 10,7257%.